A New Theory of Market and Capitalism. - Zhelezniak, Anatoliy (Cambridge Scholars Publishing, 2022)
This book presents a new theory of market and capitalism, detailing its key moments and general logic. It is based on the distinction between two market types: the simple commodity market and the capitalist one.In contrast to what is usually uncritically accepted, disequilibrium and ""imperfect competition"" are admitted here to be a functional norm of the capitalist market. The book also shows that equilibrium and ""perfect competition"" are admitted to be a functional anomaly, with crises considered as the result of such an anomaly. It details the general principles and concrete measures of.